AL-MAJMŪ’AH AL-LUGHOWIYYAH ‘ALᾹ BAHSI ILMI THULLĀB TA’LIĪM AL-LUGHOH AL-ARABIYAH FĪ JᾹMI’AH SUNAN DRAJAT LAMONGAN - Hidayah, Rohmatun Nurul; Finurika, Isna; Abidah, Zakiyatul; Rihlasyita, Wilda (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
The thesis is the final project that must be completed by all students in various departments, according to their respective majors. The Arabic Language Education at the Sunan Drajat University of Lamongan wrote their thesis in Arabic and Indonesian. In writing a thesis, only specific titles can make you bored and need more creativity. This research aims to find out what research is often done by Arabic Language Education at the Sunan Drajat University of Lamongan and is used as material for study by the Head of Arabic Language Education and evaluation in the title policy for the following year. This study uses a linguistic corpus to facilitate word search and its frequency so that it is faster, more accurate and on a large scale. The research method used is the descriptive qualitative research method. The results are qualitative and quantitative; research uses a quantitative approach with a percentage of 80% and qualitative research with a percentage of 20%. Judging from the type of research method, many use quantitative experiments, with a percentage of 76%. In terms of the dependent variable, many use the microdata element at a percentage of 24%. In terms of independent variables, many use the method with a percentage of 30%. Regarding location, there are many in Madrasah Tsanawiyah, with a percentage of 36% and Madrasah Aliyah, with a percentage of 36%.